ダイ 12 ジ ナンキョク チイキ カンソクタイ セッピョウ ブモン ガイホウ 1971 1972 ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 山田, 知充; ヤマダ, トモミ; 木村, 恒美; キムラ, ツネヨシ; 中尾, 正義; ナカオ, マサヨシ; YAMADA, Tomomi; KIMURA, Tsuneyoshi; NAKAWO, Masayoshi (国立極地研究所, 1973)
P(論文) Research work of the glaciological section of the 12th Japanese Antarctic Research Expedition (JARE 12) is outlined in this report. The section made glaciological observations in the Syowa Station area, Langhovde area, and glacial geomorphological observations along the Soya Coast. In order to conduct a pilot study of deep core drilling of ice sheet, laboratory, work shop and living quarters were constructed at the Mizuho Camp utilizing prefabricated housing material and snow tunnels. Deep core drilling was started at the end of October 1971, using newly designed mechanical and thermal drills (Figs. 4, 5, and 6), and snow/ice cores down to a depth of 75m below the surface were collected. A number of glaciological observations of the surface snow of the ice sheet by means of snow stakes and shallow boring were also made along with surface meteorological observations on the way of the over-snow traverses between Syowa Station arid Mizuho Camp (Fig. 2). The details of individual glaciological researches carried out by JARE 12 will be reported in the Antarctic Record, the Data. Reports, the Scientific Reports of JARE and other publications. departmental bulletin paper